2007
DOI: 10.1158/1055-9965.epi-07-0396
|View full text |Cite
|
Sign up to set email alerts
|

The Use of FoxP3 as a Biomarker and Prognostic Factor for Malignant Human Tumors

Abstract: Only since the early 21st century has it been proven that the immune system can actively defend the body against the development of malignant tumors. Escape from this process, termed immunosurveillance, has been shown to be required for the development of many tumors in both mice and humans, and may be a necessary prerequisite for the establishment of many malignancies. Serendipitously, an evolution in the understanding and characterization of immunosuppressor cells, regulatory T cells, has coincided with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…In this study, we investigated the correlation of FoxP3+ Tregs with tumour grades as well as with the intensity of TILs in squamous cell carcinoma of the oral cavity. We have used FoxP3 as a detection marker for Tregs as it became recently a biomarker for studying Tregs in malignant human cancers (16). We noted that Fox P3+ Tregs are consistently seen in tumour tissues but was absent in normal tissue adjacent to the tumour (in those cases where the cut margins were free of tumour).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we investigated the correlation of FoxP3+ Tregs with tumour grades as well as with the intensity of TILs in squamous cell carcinoma of the oral cavity. We have used FoxP3 as a detection marker for Tregs as it became recently a biomarker for studying Tregs in malignant human cancers (16). We noted that Fox P3+ Tregs are consistently seen in tumour tissues but was absent in normal tissue adjacent to the tumour (in those cases where the cut margins were free of tumour).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, one line of evidence showed that the presence of FoxP3+ cells within tumors has been shown to be predict the prognosis, invasiveness, and metastatic ability of some tumors by modulating the ability of the immune system to target tumor cells. The widespread use of FoxP3 as a biomarker should be explored for human tumors to enable physicians to make better decisions in oncologic care and to prepare the filed of novel therapeutic agents directed at the elimination of Treg cells within tumors (39). FoxP3 expression might be related to the metastatic potential of the tumor rather than to suppression of a specific immune response (187).…”
Section: Prognostic Value Of Treg Cells In Patients With Cancermentioning
confidence: 99%
“…In support of this notion, high levels of tumor-infiltrating CD8 + T cells, alone or combined with limited amounts of intratumoral CD4 + CD25 + FOXP3 + regulatory T cells (Tregs), have been associated with improved disease outcome upon therapy in patients affected by a variety of solid neoplasms, including (but not limited to) breast carcinoma 8 , 26 , 27 . In addition, an ever increasing amount of preclinical data indicates that the efficacy of various anticancer agents and several forms of radiotherapy depends, at least in part, on an intact immune system 28 - 32 …”
Section: Introductionmentioning
confidence: 99%